Asf2 Mediates Sir3 Availability During the Assembly of Heterochromatin - Stephenson, Sean E. K. (Université d'Ottawa / University of Ottawa, 2022)
Heterochromatin in S. cerevisiae is formed at telomeres, rDNA, and the mating type loci by the Silent Information Regulator (SIR) complex. Silencing requires the SIR complex that consists of Sir2, Sir3, and Sir4. The SIR proteins interact with each other, nucleosomes, and DNA binding proteins that are located at silencers. Although the interactions within the SIR complex are well defined, the requirements for each of these interactions during the nucleation and spreading of heterochromatin are not. This study uses genetic and biochemical techniques to assess silencing at various loci and to detect interactions between the SIR proteins. Asf2 (Anti-Silencing Factor 2) is a poorly characterized protein that interacts with Sir3 and is investigated in detail throughout this work. The overexpression of ASF2 disrupts silencing and does so by outcompeting Sir4 for Sir3 binding. ASF2 is a paralog of SIR4, and they share significant homology within their coiled-coil domains which is required for their interaction with Sir3. The Asf2 protein exists as a dimer that depends on Sir3 and may serve as a tool to alter Sir3 availability and impact heterochromatin stability. The evidence presented here categorizes the requirements for the Sir3-Sir4 interaction and the establishment of H4K16 acetylation in nucleation and spreading. Mutations in the AAA+ domain of Sir3 (sir3-4A) render it insufficient to nucleate heterochromatin but do not prevent Sir3-4A and Sir4 from spreading downstream of silencers. The Sir3-Sir4 interaction is therefore a nucleation-specific requirement. Cells lacking SAS2 are defective for telomere silencing, but silencing is partially restored by overexpressing SIR3 but not sir3-4A. Although the Sir3-Sir4 interaction is not required for Sir3 to spread on its own, Sir4/Sir2 are unable to spread without the establishment of H4K16 acetylation.
Keywords: SIR; Asf2; Heterochromatin; Saccharomyces cerevisiae